Role of Lipopolysaccharide in Protecting OmpT from Autoproteolysis during In Vitro Refolding - Gaurav Sinsinbar; Sushanth Gudlur; Kevin J Metcalf; Milan Mrksich; Madhavan Nallani; Bo Liedberg (Biomolecules, 2020)
Outer membrane protease (OmpT) is a 33.5 kDa aspartyl protease that cleaves at dibasic sites and is thought to function as a defense mechanism for E. coli against cationic antimicrobial peptides secreted by the host immune system. Despite carrying three dibasic sites in its own sequence, there is no report of OmpT autoproteolysis in vivo. However, recombinant OmpT expressed in vitro as inclusion bodies has been reported to undergo autoproteolysis during the refolding step, thus resulting in an inactive protease. In this study, we monitor and compare levels of in vitro autoproteolysis of folded and unfolded OmpT and examine the role of lipopolysaccharide (LPS) in autoproteolysis. SDS-PAGE data indicate that it is only the unfolded OmpT that undergoes autoproteolysis while the folded OmpT remains protected and resistant to autoproteolysis. This selective susceptibility to autoproteolysis is intriguing. Previous studies suggest that LPS, a co-factor necessary for OmpT activity, may play a protective role in preventing autoproteolysis. However, data presented here confirm that LPS plays no such protective role in the case of unfolded OmpT. Furthermore, OmpT mutants designed to prevent LPS from binding to its putative LPS-binding motif still exhibited excellent protease activity, suggesting that the putative LPS-binding motif is of less importance for OmpT’s activity than previously proposed.